Pengaruh Penggunaan Media Gambar Berseri terhadap Kemampuan Melengkapi Kalimat Rumpang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of using sequential picture media on students' ability to complete cloze sentences among third-grade students at MI Al-Hikmah Masangan in the 2024/2025 academic year. The research method used in this study is a quasi-experimental design with a Non-Equivalent Control Group design. The research sample consisted of two classes: the experimental class, which received treatment using sequential picture media, and the control class, which did not receive any treatment. The instrument used in this study was a cloze test that had been tested for validity and reliability. The data obtained were analyzed using statistical tests. The population in this study comprised all third-grade students at MI Al-Hikmah Masangan in the 2024/2025 academic year, totaling 28 students. Based on the results of the analysis, a significant difference was found between the experimental and control classes. This is evidenced by the hypothesis test results, which showed a significance value of 0.021 < 0.05, leading to the rejection of H0 and the acceptance of H1. Therefore, it can be concluded that the use of sequential picture media has a significant effect on the ability of third-grade students at MI Al-Hikmah Masangan to complete cloze sentences.